Detection and Analysis of ERPs for Social Cognition Evaluation (2022)
This paper describes an approach for elicitation, acquisition, and analysis of event-related potentials (ERPs) for social cognition evaluation. We used images of emotional content that were classified into three groups according to their valence: pleasant, unpleasant, and neutral. An application for stimuli generation based on the emotional oddball paradigm (EOP) was developed, and a commercial wireless EEG headset was used for signal acquisition. The ERPs of 13 volunteers for the three types of stimuli were obtained and analyzed to extract the N100 and P300 components. The results show increased amplitudes in ERP components due to unpleasant stimuli and longer latencies observed in neutral stimuli. © 2022 IEEE.